Talent Retention in SOE’s Insurance Company in Indonesia - Ginting, Agnes Salidesi; Wibowo, Risang Surya; Suwardi, Trimaryanto; Sibarani, Roza Marsaulina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Human Resources Managementis important in an organization because in practice it can facilitate the management of human resources and strategies that make their employees feel satisfied and can survive in the long term. Various challenges are being faced by many organizations in the world, where the toughest challenge today is not only how to manage its human resources, but also how to maintain them in such working conditions for as long as possible and still make a positive contribution to achieving organizational targets. Companies that want to survive in today's market must be able to identify, develop, and retain employees who are considered talents with various approaches that suit the profile of each employee. It is not impossible that with all the efforts and strategies carried out by the company in the principle of talent management, it will guarantee the position of employees to remain in the company, this is also influenced by various other factors that may be the cause of why employees want to stay in the company. Therefore, in this study the author wants to know what factors can maintain employee retention rates in the company which in this case is measured by various independent variables succession & career planning, training & development, and compensation & benefits with a population of one of the state-owned companies in Indonesia which is engaged in insurance.